Identifikasi CSF dalam Implementasi Business Intelligence di Organisasi Nirlaba: Studi Kasus di Indonesia - Hakim, Mohammad Luqmanul; Sensuse, Dana Indra; Ni Wayan Trisnawaty (The Indonesian Journal of Computer Science, 2025)
This study aims to identify and analyze the critical success factors (CSFs) for implementing business intelligence (BI) in nonprofit organizations in Indonesia. As the world's most generous country for seven consecutive years, Indonesia shows significant potential in its nonprofit sector, particularly in managing Zakat, Infaq, Sadaqah, and Waqf (ZISWAF). This research employs a systematic literature review (SLR) and a case study on a nonprofit organization adopting a BI system. The study identifies five categories of critical success factors (CSFs): organizational, technological, data management, human resource, and process factors. The findings aim to contribute theoretically and practically to digital transformation strategies in the nonprofit sector while guiding decision-makers in implementing effective and sustainable BI systems.